PERBEDAAN AREA DALAM KANDANG CLOSED HOUSE TERHADAP PERFORMA AYAM PETELUR FASE GROWER - Diantoro, Hyogi (Universitas Islam Balitar, 2023)
This study sought to ascertain how the body weight and uniformity of laying hens in the growth phase were affected by various regions in closed house cages. 480 laying hens that were still in the growth stage served as the study's subject. Surveys and observations were made in various parts of the closed-in cage as part of the research methodology. Using a paired t-test, the data were examined for body weight and homogeneity. The findings demonstrated that there was no significant impact (P>0.05) of the area difference in the closed-cage animals' body weight or on the uniformity of their average weight gain. shows a value of 92.2 grams in the front area and 96.3 grams in the outlet area. The uniformity average is 86.91% for the inlet area and 85.16% for the outlet area. In this study, it is necessary to carry out further research by including the calculation of the Heat Stress Index as an additional discussion to examine more deeply the effect of increasing body weight and uniformity.